2019
DOI: 10.3390/nu11030704
|View full text |Cite
|
Sign up to set email alerts
|

Induction of the Epithelial-to-Mesenchymal Transition of Human Colorectal Cancer by Human TNF-β (Lymphotoxin) and its Reversal by Resveratrol

Abstract: Objective: Tumor necrosis factor-beta (TNF-β), as an inflammatory mediator that has been shown to promote tumorigenesis, induces NF-κB. Natural multi-targeted agent resveratrol in turn shows anti-inflammatory and anti-cancer properties. Epithelial-to-mesenchymal transition (EMT) allows cancer cells to turn into a motile state with invasive capacities and is associated with metastasis and development of cancer stem cells (CSC). However, TNF-β-induced EMT and the anti-invasion mechanism of resveratrol on CRC are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 73 publications
3
38
0
Order By: Relevance
“…Phosphorylation of the p65-NF-κB subunit by IKKs/IκBα is a major activation step in the canonical NF-κB pathway, followed by nuclear translocation and DNA binding to modulate gene transcription [61]. Moreover, our findings are also consistent with those that have shown that numerous natural substances mediate their anti-tumorigenic potential through targeting the NF-κB pathway [19,42,[62][63][64], thereby stimulating tumor cell apoptosis and suppressing proliferation and migration. Indeed, Calebin A has recently been shown to suppress the activation of the p65-NF-κB pathway in several cell types, thereby suppressing cell growth and enhancing apoptosis [27].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Phosphorylation of the p65-NF-κB subunit by IKKs/IκBα is a major activation step in the canonical NF-κB pathway, followed by nuclear translocation and DNA binding to modulate gene transcription [61]. Moreover, our findings are also consistent with those that have shown that numerous natural substances mediate their anti-tumorigenic potential through targeting the NF-κB pathway [19,42,[62][63][64], thereby stimulating tumor cell apoptosis and suppressing proliferation and migration. Indeed, Calebin A has recently been shown to suppress the activation of the p65-NF-κB pathway in several cell types, thereby suppressing cell growth and enhancing apoptosis [27].…”
Section: Discussionsupporting
confidence: 90%
“…Indeed, previous studies have shown that Calebin A inhibits constitutive NF-κB activation as well as negatively regulating TNF-α and LPS-induced NF-κB activation [27]. We could previously show in TNF-β-stimulated CRC cells that NF-κB is a major target for the natural substance resveratrol in suppressing CRC tumor cell malignity [12,13,36,63]. Interestingly, a recent study could show that Calebin A mediates its anti-tumorogenic properties by inhibiting P300/CBP-associated factor (PCAF), which serves as transcriptional co-activator for both p53 and NF-kB [32,65].…”
Section: Discussionmentioning
confidence: 93%
“…Interestingly, previous works have shown that the chemoresistant CRC cells expressed increased several biomarkers of CSC and of epithelial-to-mesenchymal-transition (EMT), a higher capacity to become more tumor malignity (motility, proliferation, drug resistance) and developed colonospheres. It has been demonstrated that other natural compounds like curcumin, resveratrol and/or 5-FU significantly decreased CSC-and EMT-biomarkers expression in CRC cells [16,58,59]. Importantly, it is to be expected that Calebin A as a natural anti-tumor agent has a crucial target on the cancer stem cells in the tumor cell populations.…”
Section: Discussionmentioning
confidence: 99%
“…During this process, epithelial cells undergo a series of biochemical changes, which lead to the loss of polarity and migratory capacity of cells, resulting in cell shape changes (cell elongation). EMT promotes the transformation of immobile epithelial cells into motile mesenchymal cells, enhancing the metastatic properties [69,70]. Further, adherens and tight junctions become impaired, resulting in a mesenchymal phenotype [12,[71][72][73].…”
Section: Introductionmentioning
confidence: 99%